HUBUNGAN PERSEPSI KOMPENSASI, PERSEPSI PELATIHAN DAN PERSEPSI KEPEMIMPINAN TERHADAP KEPUASAN KERJA PEGAWAI PT X Tbk (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2022)
The purpose of this study was to determine the relationship between perceptions of compensation, perceptions of training, and perceptions of leadership with job satisfaction of employees. This research method uses quantitative correlational. The subjects and samples of this study were employees/ staff /employees of PT X, Tbk. with a number of 150 respondents. The sample in this study used non-probability sampling techniques, the non-probability sampling technique used was purposive sampling. Data analysis to test the hypothesis used was Kendall's tau correlation technique, used to measure the strength or relationship of two variables. The method in obtaining and collecting data that researchers do is a scale. The scale is a data collection method that is carried out by distributing a list of closed questions to the respondents so that the respondents just need to choose the answers provided. The results of this study indicate that there is a relationship between perceptions of compensation, perceptions of training, and perceptions of leadership with job satisfaction of employees. The value of the successive correlation coefficient for the relationship between perceptions of compensation, perceptions of training and perceptions of leadership on employee job satisfaction is (0.473; 0.478; and 0.553). The significant figures for all variables are 0.000, and are positive, which means the more frequent perceptions of compensation, training perceptions, and perceptions of leadership, job satisfaction is increasing.